Sollen Kriegsgedichte klar sein? Die zeitgenössische ukrainische (Kriegs-)Lyrik zwischen Verständlichkeit, Hermetik und Archaisierung - Achilli, Alessandro (Wiener Slawistischer Almanach, 2025)
In this essay, I reflect upon some theoretical and practical issues concerning contemporary Ukrainian (war) poetry and its stylistic features. While after the full-scale Russian aggression against Ukraine some poets and literary critics have observed and called for a direct, accessible kind of poetry (one able to be easily understood by a potentially large pool of readers), the actual landscape of post-2022 Ukrainian poetry shows a much more diverse variety of stylistic choices. In the initial part of my article, I discuss both critical contributions by Ukrainian authors on contemporary poetry and some leading studies on hermeticism vs. accessibility in poetry. While the bulk of my article focuses on some recent poems by Marianna Kijanovs′ka, I also discuss poetic texts by Ukrainian authors of different generations and literary orientation including Danik Zadorožnyj, Viktorija Feščuk, and Oleksandr Irvanec′. To analyze contemporary poetry’s links with tradition in light of the problem of intelligibility, I also make use of the concept of archaization, which explicitly appears in a poem by Kijanovs’ka and may explain the poetics of the poem by Irvanec′ that I discuss.